The Influence Of Trust And Service Quality On Patient Loyalty With Satisfaction As A Mediating Variable: A Case Study Of Patients At Bogor Senior Hospital (BSH) - Hanna Susila Ningsih Palupi; Nora Andira Brabo (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the influence of trust and service quality on patient loyalty with patient satisfaction as a mediating variable at Bogor Senior Hospital (BSH). The research employed a quantitative explanatory approach with a sample of 232 patients selected using simple random sampling. Data collection was conducted through structured questionnaires, and data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results show that service quality significantly influences patient satisfaction, while trust does not. Trust has a significant positive effect on patient loyalty, but service quality does not directly influence loyalty. Patient satisfaction significantly impacts loyalty and mediates the relationship between service quality and loyalty. These findings highlight that enhancing service quality and building patient satisfaction are critical strategies for fostering loyalty in healthcare services.